1988
DOI: 10.1063/1.340163
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of plate and colony precipitates decorating stacking faults in a single-crystal silicon

Abstract: Oxidation of silicon wafers containing lattice damage at the surface normally results in the formation of extrinsic stacking faults. Optical microscope investigation following decorative etching shows that on certain specimens the faults have a straight line appearance while on others the ends of the defect are much enlarged giving a ‘‘dog-bone’’ shape. Analytical electron microscopy investigation confirmed that the dog-bone shaped faults were decorated with two types of precipitates near their edges, colonies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Among these metals, Cu has been studied intensively since Dash used it to decorate dislocations in silicon crystals [1]. Precipitation of Cu in silicon proceeds by formation of Cu silicide either heterogeneously at lattice imperfections, such as dislocations [1][2][3][4][5][6], stacking faults [7,8], and grain boundaries [9], or homogeneously in the silicon lattice [10,11]. The crystal structure of the precipitates examined in the transmission electron microscope (TEM) was reported to be the 00 -Cu 3 Si phase, in which the volume per Si atom is larger than in the silicon diamond cubic lattice [12].…”
Section: Introductionmentioning
confidence: 99%
“…Among these metals, Cu has been studied intensively since Dash used it to decorate dislocations in silicon crystals [1]. Precipitation of Cu in silicon proceeds by formation of Cu silicide either heterogeneously at lattice imperfections, such as dislocations [1][2][3][4][5][6], stacking faults [7,8], and grain boundaries [9], or homogeneously in the silicon lattice [10,11]. The crystal structure of the precipitates examined in the transmission electron microscope (TEM) was reported to be the 00 -Cu 3 Si phase, in which the volume per Si atom is larger than in the silicon diamond cubic lattice [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is also fairly well established that the presence of precipitates of one metal species may aid the precipitation of another (see [10] and references therein), e.g., by providing energetically favorable nucleation sites via lattice strain or local native point defect compensation. Indeed, microscopic investigations of metal distributions in mc-Si frequently reveal multiple metals precipitated at the same location [10][11][12][13][14]. Aside from speculative arguments on the basis of elemental co-localization, no experimental evidence had concluded that metals react chemically with each other in silicon during precipitation to form alloy compounds.…”
Section: Introductionmentioning
confidence: 99%
“…3, which suggested the crystal structure of copper precipitate according to the previous work. 21 Comparing to that in the A-defect zone, copper-precipitate colony in the D-defect zone was smaller and the size of this colony consisting with many smaller copper precipitates was about 50 nm, as shown in Fig. 3͑b͒.…”
Section: Effect Of Intrinsic Point Defects On Copper Precipitation Inmentioning
confidence: 85%